ANAEROBIC POWER IN SPORTS - Stec, Krzysztof; Pilis, Karol; Witkowski, Zbigniew; Pilis, Anna; Michalski, Cezary; Zych, Michal (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the present study is to determine the anaerobic power of men of similar age representing different sports disciplines. Professional athletes representing the following sports participated in the study: soccer (n=15, PS), martial arts (n=12, MA), weightlifting (n=15, WL), powerlifting (n=15, PL), middle- and long distance running (n=12, DR), race walking (n=14, RW), and recreational soccer (n=15, RS). After recording personal and somatic data, the subjects performed a 3-minute warm-up followed immediately by a 30 seconds cycloergometric Wingate test. The following variables of anaerobic power were calculated: total external work (TEW-KJ/30s), maximal power (Pmax-W/kg), mean power (Pmean-W/kg), fatigue index (FI-%). It was shown that the examined groups differed in body weight (F=13.560, p<0.001), body height (F=3.342, p<0.01) and BMI (F=28.868, p<0.01). There were also significant differences in the TEW range (F=5.764, p<0.001), Pmax (F=2.807, p=0.013) and FI=4.942, p<0.001) and no intergroup difference in the Pmean range. In conclusion, it should be pointed out that various types of sports training develop in the various degree different components of anaerobic power, however they develop similarly its average value.